Identification of Factors Causing Wood Defects in Furniture Product Material (Flooring) Using the Fault Tree Analysis Method at PT. ABC - Rusindiyanto; Isna Nugraha; Hafid Syaifullah (Future Science, 2023)
PT. ABC is a manufacturing company specializing in the production of teak wood products, including flooring. To ensure the production of high-quality products, PT. ABC implements quality control measures, starting with the identification of product defects to minimize process errors. The goal of this research is to identify product defects at PT. ABC and determine the root causes of these defects using the Fault Tree Analysis (FTA) method. Additionally, the study aims to provide improvement suggestions for preventing and reducing potential causes of product defects. The results of this research indicate that the main defect is related to incorrect dimensional size. During product sampling within the initial 180 minutes of the production process, the probability of incorrect size is 15.69%, followed by lumps with a probability of 11.21%, and rough surface with a probability of 8.20%. Areas requiring improvement include: 1. Workforce: Skilled and disciplined personnel are needed to follow procedures and equipment specifications in the flooring production process at PT. ABC; 2. Process: Maintenance activities should be enhanced, and regular checks should be conducted as necessary.